PENGARUH RELOKASI TERHADAP SOSIAL DAN EKONOMI PEDAGANG DI PASAR ATAS BUKITTINGGI - Dwifany Yodina Putri; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at Bukittinggi precisely at the Lokasi Penampungan Sementara Pasar Atas (ateh), Jalan Jam Gadang, Kelurahan Benteng Pasar Atas (ateh), Kecamatan Guguk Panjang. This research aim to know the impact caused by relocation. The focus of this research is on social and economic impacts after the relocation of the Pasar Atas (ateh) Bukittinggi. Simple Random Sampling technique for sampling and determined a total sample of 54 people. The author used quantitative descriptive methods and data instruments in this research are observation, guided interviews and documentation. The study found a comparison between social impact and economic impact, namely, the social impact was categorized as "very high" with a percentage of 55.6%, while the economic impact was categorized as "medium" with a percentage of 72.2%. This means that in this study the social impact is more dominant.Keywords: Relocation, Impact, Social, Economy